Stationary measures on infinite graphs - Baraviera, Alexandre (2022)
We extend the theory of isospectral reductions of L. Bunimovich and B. Webb to infinite graphs, and describe an application of this extension to the problems of existence and approximation of stationary measures on infinite graphs.